Macroeconomic effects of world oil and food price shocks in Asia and Pacific economies: application of SVAR models - Alom, Md. Fardous; Ward, Bert D.; Hu, Baiding (Wiley Blackwell, 2013)
This study, by employing structural vector auto regression models, investigates the macroeconomic effects of world oil and food price shocks in the context of selected Asia and Pacific countries. The study reveals that the economic activities of resource-poor countries that specialise in heavy manufacturing industries, like Korea and Taiwan, are highly affected by world oil price shocks. On the other hand, the economic activities of oil-poor nations such as Australia and New Zealand, with diverse mineral resources other than oil, are not affected by oil price shocks. Furthermore, countries that are oil poor but specialise in international financial services, such as Singapore and Hong Kong, are also not affected by oil price increases. Moreover, some developing countries, in this case, India, with limited reserves of oil are not affected by oil price shocks, whereas other such countries, like Thailand, possessing a number of natural resources other than oil are more strongly affected by oil price shocks. With regard to food price shocks, limited impacts from food price increases can be recorded for India, Korea and Thailand. Overall, the effects of external oil and food prices depend on the economic characteristics of the countries.